2021
DOI: 10.24875/bmhim.20000255
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal unplanned extubations: an unsolved safety issue

Abstract: Background: Unplanned extubations are safety events relatively frequent in the neonatal intensive care units (NICU). This study aimed to describe the frequency and characteristics of unplanned extubations in a NICU. Methods: We conducted a retrospective observational study of unplanned extubations in the NICU of a tertiary regional referral hospital. We reviewed medical records for data collection and performed the statistical analysis, comparing the cases of unplanned extubations with those in which it did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Similar to the observations reported by others, we observed that the smallest [ 5 , 25 ] and most premature infants [ 5 ] were those who most frequently experienced UEs during our project. These patients have anatomical challenges and often require prolonged mechanical ventilation, which contributes to an increased likelihood of experiencing UE [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the observations reported by others, we observed that the smallest [ 5 , 25 ] and most premature infants [ 5 ] were those who most frequently experienced UEs during our project. These patients have anatomical challenges and often require prolonged mechanical ventilation, which contributes to an increased likelihood of experiencing UE [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…To address this, we anticipate the implementation of an extubation readiness protocol, which may optimize the timing of extubation in our high-risk population. 33 Additionally, we have not yet explored the use of sedation in our NICU population. Because agitation can contribute to UE, careful consideration of analgesia/sedation in high-risk patients is warranted.…”
Section: Discussionmentioning
confidence: 99%